Effects of drying and salt extraction of Moringa oleifera on its coagulation of high turbidity water - Montakhab, Amir; Ghazali, Abdul Halim; Megat Mohd Noor, Megat Johari; Mohammad Ali, Thamer Ahmad; Yusuf, Badronnisa (Marsland Press, 2010)
Moringa oleifera (M.O.) has been used as a natural coagulant in water treatment. The present study aims to determine the effect of drying M.O. seed powder that has been extracted with salt (NaNO3) on the coagulation of synthetic (kaolin) water of 200±5 NTU. The optimum quantity of M.O. was 5 mg for both 10 and 200 g/l concentrations of the non-spray-dried salt-extracted M.O. (MOC-SC) solutions, with turbidity removal of 87%. This maximum turbidity removal was achieved with 1 M and 0.5 M of NaNO3 salt in the former and latter concentrations, respectively. The spray-dried M.O. (MOC-SC-SD) solutions exhibited better maximum turbidity removal of more than 95%, which also occurred at 5 mg of M.O., for both concentrations. Finally, the duration of storage of MOC-SC-SD did not affect its performance in the removal of turbidity.